Usability Evaluation of Virtual Reality Metaverse Lab Using Usability Testing With the User-Centered Design Approach - Ketut Sepdyana Kartini; I Made Marthana Yusa; I Nyoman Widhi Adnyana; I Nyoman Tri Anindia Putra (International Journal of Engineering, Science and Information Technology, 2025)
Advances in educational technology have introduced immersive tools such as Virtual Reality (VR) to support complex learning, especially in abstract fields like chemistry. Metaverselab was developed to provide a safe virtual environment for conducting laboratory experiments, yet early implementation revealed substantial usability issues. Students experienced difficulties with the interface, confusion in navigation, and insufficient guidance, which affected the overall learning experience. This study aims to evaluate and improve the usability and user experience of the Metaverselab platform using a User-Centered Design (UCD) approach. The research applied an iterative process involving 40 student respondents and used two standardized instruments: the System Usability Scale (SUS) and the User Experience Questionnaire (UEQ). Both instruments were administered during the initial and final evaluation stages to measure changes in usability and user experience after improvements were introduced. Initial results showed low usability, with an average SUS score of 50.81 and UEQ benchmark values categorized as “Bad” in all dimensions. Based on these findings, specific user requirements were identified and translated into targeted design solutions. Key improvements included an interactive tutorial for first-time users, descriptive information pop-ups for laboratory tools, and undo–redo functions to support error recovery during experiments. Post-implementation testing demonstrated substantial improvement. The average SUS score increased by 44.16% to 73.25, placing the system in the “Good” usability category. UEQ results also improved significantly, with the Efficiency dimension rated “Excellent,” while Attractiveness, Perspicuity, and Stimulation were rated “Good.” These results confirm that the UCD approach effectively identifies user needs and produces design interventions that enhance the usability, efficiency, and overall learning experience of virtual educational platforms.